Artificial Intelligence and the Development of Smart Tourism - GENÇ, Ruhet (Journal of Tourism and Hospitality Education, 2020)
The main intention of this manuscript is to fill this gap by evaluating the impacts of artificial intelligence on the development of smart tourism. The study will start with discussing previous literature on smart tourism and contributions of artificial intelligence on the development of tourism based on earlier academic findings and practical implications. For methodology, the paper will follow literature review as a guideline and the findings will be critically evaluated. Besides that, the study will suggest a model whereby the impact of artificial intelligence on smart tourism will be quantitatively analyzed. In the suggested model, related economic, technological, social and environmental variables including total revenue created by smart tourism using artificial intelligence, contributions of technological improvement, the degree of social inclusion to tourism activities for disadvantaged individuals (such as elderly, people with disabilities, pregnant women etc.) with respect to the artificial intelligence applications, and the degree of environmental degradation parallel to the shift to smart tourism.